2015
DOI: 10.1093/brain/awu409
|View full text |Cite
|
Sign up to set email alerts
|

Eltoprazine counteracts l-DOPA-induced dyskinesias in Parkinson’s disease: a dose-finding study

Abstract: See Bezard and Carta for a scientific commentary on this article (doi:).In a double-blind placebo-controlled study, Svenningsson et al. test a single oral dose of eltoprazine—a serotonin 5-HT1A/1B receptor agonist—plus L-DOPA in patients with Parkinson's disease and L-DOPA-induced dyskinesias. Eltoprazine doses of 5 mg and 7.5 mg are well-tolerated, and have antidyskinetic efficacy without altering motor responses to L-DOPA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
66
0
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 143 publications
(70 citation statements)
references
References 34 publications
3
66
0
1
Order By: Relevance
“…Our observation that evoked glutamate release is reduced in p11KO mice provides additional support for a blunted glutamatergic neurotransmission in these mice. Because both 5-HT 1A/B R agonists and mGluR5 antagonists have shown antidyskinetic properties in PD patients with LIDs (22,23), it will be important to further delineate the pathways whereby p11 influences serotonergic and glutamatergic mechanisms underlying LIDs.…”
Section: Discussionmentioning
confidence: 99%
“…Our observation that evoked glutamate release is reduced in p11KO mice provides additional support for a blunted glutamatergic neurotransmission in these mice. Because both 5-HT 1A/B R agonists and mGluR5 antagonists have shown antidyskinetic properties in PD patients with LIDs (22,23), it will be important to further delineate the pathways whereby p11 influences serotonergic and glutamatergic mechanisms underlying LIDs.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, silencing of serotonin neuron activity by 5-HT1 receptor agonists has been shown to produce near-complete suppression of LID in experimental models of PD [1,4,7,9,12,22]. Most interestingly, eltoprazine was recently shown to produce significant reduction of LID in dyskinetic patients [11]. However, although in the Svenningsson study no exacerbation of the PD motor disability was found after eltoprazine administration, several preclinical and clinical studies reported a reduction of the therapeutic effects of l-DOPA and induction of serotonin syndrome after 5-HT1 receptor activation [6,7,14], raising concerns for clinical feasibility of this approach to counteract dyskinesia.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, in a situation of advanced PD stage, when most of DA neurons have degenerated, DA is released via serotonergic neurons in a pulsatile, non-physiological manner, leading to abnormal stimulation of the supersensitive post-synaptic striatal DA receptors, and development of dyskinesia [1,[3][4][5]. Accordingly, the use of serotonin 5-HT1 receptor agonists to dampen serotonergic neuron activity, and in turn DA release, is effective in reducing LID in both pre-clinical and clinical studies [4][5][6][7][8][9][10][11]. http However, administration of 5-HT1 receptor agonists to dyskinetic animals and patients is associated with worsening of PD symptoms [7,[12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…12,28 In humans, a recent clinical and PET imaging study from our group showed that buspirone, a 5-HT1a partial agonist, when administered acutely prior to levodopa in patients with PD with LIDs, is able to normalize levodopa-derived levels of synaptic dopamine and to alleviate dyskinesias. 12 Similarly, a recent phase I/IIa clinical trial in patients with PD 29 confirmed antidyskinetic effects of the 5-HT1a/5-HT1b partial agonist eltoprazine following the promising results of the same drug in 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP)-treated macaques. 12 Taken together, these studies suggest that the development of LIDs is dependent on compromised dopaminergic function and on aberrant serotonergic function in the striatum.…”
mentioning
confidence: 90%